Digital Skills and Self-employment among Graduates of Technical Higher Education Institutions in Tanzania - Raphael, Charles (Tanzania Journal of Engineering and Technology, 2022)
Digital skills are the driving forces for innovative, inclusive and sustainable growth through innovations and digitalization which in turn stimulate job creation, alleviate poverty, reducing inequality, facilitating the delivery of goods and services. However, large number of graduates is shown to be weak in digital skills in the industry hence affect their employability including self-employment. Recently, the Technical Higher Education Institutions (THEIs) took some initiatives to instill the digital skills to their respective students. This study therefore assessed the level of competence of digital skills among graduates following the initiatives taken by the THEIs and their influence on self-employment. It specifically identified the digital skills and ranking the digital skills acquired by the graduates when in the THEIs. It likewise established relationship between digital skills and self-employment among the graduates. The data were collected using a questionnaire from 500 graduates sampled through a stratified random sampling technique. The collected data were analyzed using Descriptive Statistics and Chi-square. The findings show that, the surveyed graduates acquired basic digital skills (i.e. creating professional online profiles, word processing, using keyboards and touch-screens, managing privacy settings, emails) to the large extent (53%); intermediate digital skills (i.e. desktop publishing, digital graphic design, digital marketing) to the small extent (52%) and advanced digital skills (i.e. big data, artificial intelligence, digital entrepreneurship, cybersecurity, internet of things, virtual reality) to the very small extent (54%) when in the college/university. Furthermore, intermediate and advanced digital skills were ranked higher as digital skills for self-employment by the graduates. All three digital skills were found positive and significant for self-employment among the graduates in Tanzania. The study recommends that, the colleges, institutes and universities should emphatically inculcate all the digital skills to the students as they are both significant for self-employment of their respective graduates. Keywords: Digital skills, self-employment, and graduates